Principal Supervision Management to Enhance Teacher Professional Competence - Ani Nuraeni; Hanafiah Hanafiah (Journal of Science and Education (JSE), 2026)
The principal's role as an instructional supervisor is critical for fostering teacher professional competence, a key determinant of educational quality. However, a significant gap often exists between the policy mandate for supervision and its effective implementation. This study aims to analyze the management of principal supervision in enhancing the professional competence of elementary school teachers. This research employed a qualitative approach with a multiple-case study design at two Indonesian public elementary schools, SDN Padamamur and SDN Jambudipa 1. Data were collected through in-depth interviews with principals and teachers, non-participant observations of supervisory activities, and analysis of institutional documents. Data credibility was ensured through source and technique triangulation, and the analysis followed the interactive model of Miles and Huberman. The findings reveal that both principals managed supervision through systematic planning, organization, implementation, and evaluation. Planning was based on teacher needs assessments and school quality targets. Implementation utilized a clinical supervision model (pre-conference, observation, post-conference) with developmental and humanistic approaches. Evaluation was integrated with the formal Teacher Performance Appraisal (PKG) system and followed by targeted professional development. The management approach directly contributed to measurable improvements in teachers' professional competence. The effective management of supervision is a powerful mechanism for improving teacher competence. This study concludes that a structured, developmental, and collaborative supervisory process, managed systematically by the principal, is essential for translating policy into impactful practice. It recommends strengthening principals' capacity to lead supervision as a continuous cycle of professional learning rather than an administrative compliance task.